Muslim Brotherhood Activity in Egypt (20th – Early 21st Centuries) - Луценко, Н. (Київський національний університет імені Тараса Шевченка, 2020)
The article examines the origins of political Islam in the Middle East and the terminological aspect of the problem. The stages of the formation of the Egyptian Islamic organization Muslim Brotherhood were clarified and its key ideological tenets were established. The political and socio-economic circumstances in which the organization was formed are outlined. Attention is drawn to the collapse of the Ottoman Empire, the military and economic presence in Egypt of the United Kingdom, which consolidated political Islamic parties. The process of transforming the Muslim Brotherhood from a "group of like-minded people" into a political party is considered. The political and legal ideas of the founder of the organization Hasan al-Banna are covered. which became the main strategy of the Muslim Brotherhood. The situation of the organization in the 30's and 40's was analyzed during the attempt of Nazi Germany to turn the Brothers into their own puppet. The article reveals the role in the organization of its ideologist Said Qutb. His main ideas and views, which formed the basis of the radical Muslim Brotherhood branch, are analyzed. The link between the radicalism of the organization and the ultra-conservative trend of Islam – "Salafism" – was noted. The connection of the Muslim Brotherhood with the Free Officers organization, which came to power in Egypt in 1952, has been disclosed. It was stated that the Brothers supported General Gamal Nasser in the struggle for power, which allowed them to take part in the parliamentary elections. It is stated that the Brothers' criticism of the policies of Gamal Nasser and Anwar Sadat on Israel led to a ban of the organization's activities in Egypt. It has been established that under the presidency of Hosni Mubarak, the "Brothers" tried to enter parliament in other parties. The place and role of the organization during the Egyptian Revolution of 2011, which led the Muslim Brotherhood to power, were examined. The main reasons for the failure of the organization are indicated.

Досліджено зародження політичного ісламу на Близькому Сході та термінологічний аспект проблематики. З'ясовано етапи становлення єгипетської ісламської організації "Брати-мусульмани" та встановлено її ключові ідеологічні постулати. Окреслено політичні та соціально-економічні обставини, у яких відбувалося становлення організації. Звертається увага на розпад Османської імперії, військово-економічну присутність у Єгипті Великої Британії, що консолідувало політичні ісламські партії. Розглянуто процес трансформації "Братів-мусульман" із "групи однодумців" у політичну партію. Висвітлено політико-правові ідеї засновника організації Хасана аль-Банни. які стали головною стратегією "Братів-мусульман". Проаналізовано становище організації у 30–40-х рр., під час спроби нацистської Німеччини перетворити "Братів" на власну маріонетку. Розкрито роль в ораганізації її ідеолога Саїда Кутба. Проаналізовано його головні ідеї та погляди, що лягли в основу радикальної гілки "Братів-мусульман". Зазначено про зв'язок радикалізму організації з ультраконсервативним напрямом ісламу – "салафізмом". Розкрито зв'язок "Братів-мусульман" з організацією "Вільні офіцери", що прийшли до влади у Єгипті у 1952 р. Зазначено, що "Брати" підтримали генерала Гамаля Насера у боротьбі за владу, що дозволило їм узяти участь у парламентських виборах. Показано, що критика "Братами" політики Гамаля Насера та Анвара Садата щодо Ізраїлю призвела до заборони діяльності організації у Єгипті. Встановлено, що за президентства Хосні Мубарака "Брати" намагалися увійти в парламент у складі інших партій. Досліджено місце та роль організації під час єгипетської революції 2011 р., внаслідок якої "Братам-мусульманам" вдалося прийти до влади. З'ясовано головні причини поразки організації.
Діяльність «братів-мусульман» у Єгипті (XX – початок XXI ст.)
Keywords: Islam; Islamism; Political Islam; Muslim Brotherhood; Egypt; іслам; ісламізм; політичний іслам; Брати-мусульмани; Єгипет